Determinan Non Performing Financing dengan Inflasi Sebagai Variabel Moderasi Pada Bank Umum Syariah - Sistiyarini, Evi (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2025)
In providing loan facilities in the form of financing to customers, every Islamic bank needs to apply the principle of prudence by conducting proper analysis and good management. This is expected to reduce the risk of non-performing financing so that the NPF of Islamic banks can decrease. Increasing NPF in banks can increase risk and lower bank profits. There are 5 independent variables, namely FDR, BOPO, bank size, GDP and exchange rate. The moderation variable used is inflation. The dependent variable is NPF. The research sample consisted of 10 Sharia Commercial Banks taken by purposive sampling method in the first quarter of 2019 to the fourth quarter of 2023. This study uses the panel data regression method and Moderated Regression Analysis with the eviews program. The results of the analysis showed that partially the variables FDR, BOPO, GDP and Exchange Rate had a non-significant negative influence on NPF, while the bank size variable had a significant negative influence on NPF. The inflation variable as a moderation variable is able to moderate the influence of FDR and measures significantly on NPF.